-k-5k=-k-4

Simple and best practice solution for -k-5k=-k-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -k-5k=-k-4 equation:



-k-5k=-k-4
We move all terms to the left:
-k-5k-(-k-4)=0
We add all the numbers together, and all the variables
-k-5k-(-1k-4)=0
We add all the numbers together, and all the variables
-6k-(-1k-4)=0
We get rid of parentheses
-6k+1k+4=0
We add all the numbers together, and all the variables
-5k+4=0
We move all terms containing k to the left, all other terms to the right
-5k=-4
k=-4/-5
k=4/5

See similar equations:

| 3(b-14)-6=6 | | .5x+20=2x-10 | | 26-2x=54 | | 3x+24=15-2x | | 12x^2=44x | | 18t-16=-2 | | 4x+15=2x+13 | | -g+2(3+1g)=-4(g+1) | | 5x-(2x-7)=3(-2x+1) | | 13x-9x+5+3=12 | | 7x+133=14 | | -1/3+6/5y=-3/2 | | 5x+3=x025 | | 10f-0.6=22.5 | | -16=-4+2y | | -2w+8=20 | | 9x=3x+2 | | 5x-5=-7+4x | | 8+w/4=6 | | 9v+6=15 | | x+25+6x-20+5x+3x+10=360 | | 20x^2-72x-140=0 | | 9(u+2)=18 | | 5x+22=x-2 | | 6(x+1)=-54 | | 2x(x+9)-15=-3 | | 4(x-2)-2x=4x-2 | | x-11/2=8 | | 2(2x-5)=3x-3 | | 6x+21=2x+5 | | r/18+1=6 | | 3(x-1)^2-1=11 |

Equations solver categories